BRAND AWARENESS AND BRAND IMAGE ON THE PURCHASE DECISION OF MIE GACOAN - Winsi, Delinta Melati Putri; Yuliana, Lingga (JMK (Jurnal Manajemen dan Kewirausahaan), 2026)
This study aims to examine the influence of brand awareness and brand image on purchasing decisions using the Mie Gacoan brand as a case study. The research method chosen is quantitative research. The sampling technique used is purposive sampling. A total of 100 respondents were involved in this study. Respondents were male and female aged 12 years and above, residing in Indonesia, and purchasing Mie Gacoan products. The data source used primary data by distributing questionnaires through Google Forms. The measurement scale applied was a five-point Likert scale, with a value range of 1 to 5. Furthermore, the data was analyzed using the Partial Least Square (PLS) method to test the relationship between the variables studied, using SmartPLS version 4.1.0.0. The results showed that brand awareness had a significant and positive effect on purchasing decisions. Similarly, brand image had a significant and positive effect on purchasing decisions.